(untitled) (Marketing Journal, 2025)
The trade relations between Uzbekistan and India have grown stronger in recent years. The economic partnership has flourished, driven by countries’ mutual interests in trade, investment, and regional connectivity. This study makes an attempt at understandi ng the role of Uzbekistan’s institutional frameworks in facilitating the Indian investment in the country. The study also aims to analyze the factors that are shaping economic relationships between the countries. Factors like bilateral agreements, regulato ry policies, and diplomatic initiatives are considered here. This article aims to highlight and challenges for the Indian investors in Uzbekistan by thoroughly analysing the historical context, current economic situations, ties between the countries, and i nstitutional mechanisms. This study also aims at providing workable recommendations for strengthening institutional frameworks to improve investment flows in future. Drawing on secondary data collected from published researches, international commerce dat a, government reports, and academic literature, this article shall contribute to the improved understanding of how the institutional frameworks pertaining to foreign investments influence cross -border investment in emerging economy of Uzbekistan.